2024
DOI: 10.3390/fishes9050151
|View full text |Cite
|
Sign up to set email alerts
|

Triple Attention Mechanism with YOLOv5s for Fish Detection

Wei Long,
Yawen Wang,
Lingxi Hu
et al.

Abstract: Traditional fish farming methods suffer from backward production, low efficiency, low yield, and environmental pollution. As a result of thorough research using deep learning technology, the industrial aquaculture model has experienced gradual maturation. A variety of complex factors makes it difficult to extract effective features, which results in less-than-good model performance. This paper proposes a fish detection method that combines a triple attention mechanism with a You Only Look Once (TAM-YOLO)model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Jubayer et al [22] found that the overall performance of YOLOv5 in detecting mould on food surfaces was superior to that of YOLOv4 and YOLOv3, achieving an average precision of 99.6%. Long et al [23] developed a system for fish detection, where YOLOv5 also obtained the highest mAP value of 95.95%, superior to YOLOv3 and YOLOv4. Ahmad et al [24] conducted a study comparing the performance of YOLO-Lite, YOLOv3, YOLOR, and YOLOv5 in identifying insect pests, with YOLOv5 emerging once more as the most successful, achieving an average precision of 98.3%.…”
Section: Machine Learning and Deep Learningmentioning
confidence: 99%
“…Jubayer et al [22] found that the overall performance of YOLOv5 in detecting mould on food surfaces was superior to that of YOLOv4 and YOLOv3, achieving an average precision of 99.6%. Long et al [23] developed a system for fish detection, where YOLOv5 also obtained the highest mAP value of 95.95%, superior to YOLOv3 and YOLOv4. Ahmad et al [24] conducted a study comparing the performance of YOLO-Lite, YOLOv3, YOLOR, and YOLOv5 in identifying insect pests, with YOLOv5 emerging once more as the most successful, achieving an average precision of 98.3%.…”
Section: Machine Learning and Deep Learningmentioning
confidence: 99%